ASSOCIATION NOTES. - Austin, E. Burl (The Accounting Review, 1950)
This article discusses various developments related to the field of accounting. In Great Britain, the Association of University Teachers of Accounting held its 1950 conference at Manchester University in September. The secretary of the Association is David Solomons of the London School of Economics. In the George Washington University, Ralph Dale Kennedy, currently head of the department of business administration, has been named head of the newly created department of accounting. In Catholic University of America, District of Columbia, Richard J. Bannon has been appointed instructor in accounting. In University of Alabama, Alabama, Richard Brewer is on leave for the current year teaching at the University of Hawaii. Lee Glover from Hawaii is teaching here on an exchange basis. At University of San Francisco, California, A. D. McNeil, director of CPA training, addressed the California Society of CPA's on the impact of accounting on government and business, at their annual meeting in San Francisco in June.